Fish consumption and socio-economic factors among residents of Arkhangelsk city and the rural Nenets autonomous area - Petrenya, Natalia Nikolaevna; Dobrodeeva, Lilya; Brustad, Magritt; Bichkaeva, Fatima; Menshikova, Elena; Lutfalieva, Gulnara; Poletaeva, Anna; Repina, Veronika; Cooper, Marie; Odland, Jon Øyvind (University of Oulu, 2011)
The urban Russian and the rural Indigenous populations in the Russian European North have different lifestyles, living conditions and food supplies. The objective of this study was to investigate and compare fish consumption in relation to the socio-economic characteristics of communities in Arkhangelsk County. This is a cross-sectional study. In total, 166 adults (83.1% women) from Arkhangelsk city and 134 adults (80.6% women) from the village of Nelmin-Nos (of which 88.9% are Indigenous people, Nenets), in the Nenets Autonomous Area (NAO), attended a health screening. The screening included a physical examination, blood sampling and a questionnaire. The populations studied had different socio-economic characteristics. In the rural NAO group, education levels were lower, the number of full-time employees was less, the percentage of persons with low monthly income was higher and the number of children per household was higher when compared to the Arkhangelsk group. The median total fish intake was 48.8 g/day for Arkhangelsk city and 27.1 g/day for Nelmin-Nos (p=0.009). Locally caught whitefish constituted a major part of the total fish consumption in Nelmin-Nos, while lean marine fish species were rarely eaten. Cod and cod-family fish species were often consumed by residents of Arkhangelsk city (p<0.001). Fish consumption was positively related to monthly income. The frequency of fishing in the respondents from the Nelmin-Nos group predicted their fish consumption. Monthly income had a significant influence on fish intake in both study populations from Northern Russia. Fishing seems to be an important factor for predicting fish consumption in the residents of the rural NAO.